Decoding Digital Eco-Persuasion: Semiotic Strategies and Brand Identity in Honda’s Hybrid YouTube Campaigns - Dindin Saepul Kholik; Ismail Dursun (Universitas Tribhuwana Tungga Dewi, 2026)
The growing global adoption of hybrid electric vehicles, including in the Turkish market, has intensified competition among car manufacturers to effectively communicate technological sophistication and environmental responsibility via social media, particularly YouTube, as this increasingly shapes consumer perceptions and purchasing decisions in the automotive sector. Understanding the semiotic strategies employed in this context is therefore of paramount importance. This study analyses marketing communication in YouTube advertisements through a case study of four Honda e: HEV adverts published on the official Honda Türkiye channel. Using Roland Barthes’ qualitative semiotic approach, the analysis covers the denotative, connotative, and mythical levels to identify the signs, codes, and green narratives used to convey the marketing message. The findings indicate that the Honda e: HEV relies on a combination of visual symbols, technological features, and narrative structures to build an environmentally conscious brand identity, position hybrid technology as a clean solution for the future, and shape the audience’s perception of eco-friendly automotive innovation. In theory, this study extends Barthes’ framework beyond its traditional print and image-based context by demonstrating its application to short-form digital video, a temporally sequential, multimodal format applied to eco-friendly product campaigns. In practice, this study offers recommendations for advertising practitioners seeking to create more targeted promotional messages for hybrid and green technology products on social media platforms.